2021
DOI: 10.1038/s41598-021-95568-5
|View full text |Cite
|
Sign up to set email alerts
|

A simple and fast spectroscopy-based technique for Covid-19 diagnosis

Abstract: The coronavirus pandemic, which appeared in Wuhan, China, in December 2019, rapidly spread all over the world in only a few weeks. Faster testing techniques requiring less resources are key in managing the pandemic, either to enable larger scale testing or even just provide developing countries with limited resources, particularly in Africa, means to perform tests to manage the crisis. Here, we report an unprecedented, rapid, reagent-free and easy-to-use screening spectroscopic method for the detection of SARS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 50 publications
5
25
0
Order By: Relevance
“…Saliva FTIR spectra of this COVID.POS FU.NEG group displayed reduced saccharide (ribose) bands (1038 cm −1 and 1074 cm −1 ) compared with COVID.POS FU.POS . These bands coincided with the ATR-FTIR bands for extracted SARS-CoV-2 RNA [53], in agreement with the PCR results; however, this difference in saccharide absorbance may also indicate recovery from the previously described, hyperglycemic state. This group also showed reduced signal in the finger print region, proposed by Martinez-Cuazitl et al [9] to represent immunoglobulins IgG, IgM, and IgA.…”
Section: Discussionsupporting
confidence: 88%
“…Saliva FTIR spectra of this COVID.POS FU.NEG group displayed reduced saccharide (ribose) bands (1038 cm −1 and 1074 cm −1 ) compared with COVID.POS FU.POS . These bands coincided with the ATR-FTIR bands for extracted SARS-CoV-2 RNA [53], in agreement with the PCR results; however, this difference in saccharide absorbance may also indicate recovery from the previously described, hyperglycemic state. This group also showed reduced signal in the finger print region, proposed by Martinez-Cuazitl et al [9] to represent immunoglobulins IgG, IgM, and IgA.…”
Section: Discussionsupporting
confidence: 88%
“…Kitane et al [ 26 ] had reported an unparalleled, fast, reagent-free, and user-friendly screening spectroscopic method for the detection of SARS-CoV-2 on RNA extracts. This method was verified on clinical samples collected from 280 patients with quantitative predictive scores on both positive and negative samples.…”
Section: Ftir Spectroscopy–based Detection Of Covid-19mentioning
confidence: 99%
“…2 The schematic diagram exhibiting sequential FT-IR-based assay for the detection of SARS-CoV-2, which consisted of sample collection, RNA extraction, FTIR analysis, and subsequent machine learning. (Reprinted with permission from Kitane et al [ 26 ]. Copyright (2021) Nature Portfolio) …”
Section: Ftir Spectroscopy–based Detection Of Covid-19mentioning
confidence: 99%
“…Nasopharyngeal samples collected from 280 patients were processed to extract the RNA. The FTIR spectral domains lying at 600‐1350 cm −1 ; 1500‐1700 cm −1 ; and 2300‐3900 cm −1 were attributed to RNA fingerprints [ 20 ]. The derivatives of the raw spectra obtained were used to normalize the data of the transformed spectra; machine learning algorithms were used to build classification models.…”
Section: Molecular Spectroscopic Techniquesmentioning
confidence: 99%